Bone marrow CD169+ macrophages promote the retention of hematopoietic stem and progenitor cells in the mesenchymal stem cell niche - Chow, Andrew; Lucas, Daniel; Hidalgo, Andrés; Méndez-Ferrer, Simón; Hashimoto, Daigo; Scheiermann, Christoph; Battista, Michela; Leboeuf, Marylene; Prophete, Colette; van Rooijen, Nico; Tanaka, Masato; Merad, Miriam; et al. (The Journal of experimental medicine, 2011)
Hematopoietic stem cells (HSCs) reside in specialized bone marrow (BM) niches regulated by the sympathetic nervous system (SNS). Here, we have examined whether mononuclear phagocytes modulate the HSC niche. We defined three populations of BM mononuclear phagocytes that include Gr-1hi monocytes (MOs), Gr-1lo MOs, and macrophages (MΦ) based on differential expression of Gr-1, CD115, F4/80, and CD169. Using MO and MΦ conditional depletion models, we found that reductions in BM mononuclear phagocytes led to reduced BM CXCL12 levels, the selective down-regulation of HSC retention genes in Nestin+ niche cells, and egress of HSCs/progenitors to the bloodstream. Furthermore, specific depletion of CD169+ MΦ, which spares BM MOs, was sufficient to induce HSC/progenitor egress. MΦ depletion also enhanced mobilization induced by a CXCR4 antagonist or granulocyte colony-stimulating factor. These results highlight two antagonistic, tightly balanced pathways that regulate maintenance of HSCs/progenitors in the niche during homeostasis, in which MΦ cross talk with the Nestin+ niche cell promotes retention, and in contrast, SNS signals enhance egress. Thus, strategies that target BM MΦ hold the potential to augment stem cell yields in patients that mobilize HSCs/progenitors poorly.